Haunted Halloween : movie novel - Stine, R. L. (New York, NY : Scholastic Inc., 2018)
"When Sonny and Sam find a ventriloquist dummy labeled "Slappy" in an abandoned house and bring him home, the dummy comes to life, and soon begins using dark magic powers to make Halloween a living nightmare in town." --
At head of title: Goosebumps.
620L
Decoding demand: 95 (very high) Semantic demand: 100 (very high) Syntactic demand: 89 (very high) Structure demand: 88 (very high)
Keywords: Ventriloquists' dummies -- Juvenile fiction; Halloween -- Juvenile fiction; Horror fiction; Humorous fiction